The Influence Of English Phrase Videos On Improving Speaking Skills Of Course Participants At LKP Incredible - Emirati Emirati; Ilmar Andi Achmad; Mutmainnah Marzuki; Nur Ina Syam; Andi Anugrah M (Innovative: Journal Of Social Science Research, 2023)
The study's purpose is to see how English Phrase Videos affect the speaking skills of LKP Incredible course participants. A pre-experimental design including a pre-test and a post-test was employed by the researcher. The population for this study was drawn via purposive sampling from the intermediate grade of LKP Incredible, Bulukumba in the academic year 2021/2022. There are 12 students in this sample. The data analysis demonstrated a significant difference in students' speaking competence between pre-test and post-test, notably in students' pronunciation and vocabulary following therapy. The pupils' pre-test mean score was 41.66, while their post-test mean score was 60. It was revealed that the pupils' post-test scores were greater than their pre-test scores. The t-test value was 8.85, which was greater than the t-table 1.795 at the level of significance () = 0,05 and degree of freedom (df) =12 -1=11. The t-test value (8.85 > 1.795) was determined to be greater than the t-table value. It denotes that hypothesis H0 was rejected and hypothesis H1 was accepted. The use of video of English sentences increases learners' pronunciation and vocabulary, according to this study. According to the study, teachers would use video of English phrases as one of the media in the teaching and learning process, particularly in teaching speaking.